DOZ047.67: Comparison of mesenchymal stem cells from pediatric normal and esophageal atresia patients for use in regenerative medicine. (24th June 2019) - Jensen, T; Wanczyk, H; Thaker, S; Mitchell, A; Sharma, I; Finck, C
Abstract: Esophageal atresia (EA) is a congenital defect in which the esophagus is not fully connected. Current treatments to bring together long gaps between the esophagus have very high complication rates and the replacement tissue does not possess the correct structure or physiologic properties. Tissue engineering and regenerative medicine have been suggested as a new patient-specific treatment for EA utilizing the patient's own cells and a tubular scaffold. Our group recently published on the successful regeneration of an esophagus using a retrievable scaffold seeded with adipose derived mesenchymal stem cells (AD-MSC) in a porcine model of esophageal loss. The goal of this study is to evaluate phenotypic differences between AD-MSCs from normal (N-AD-MSC) and EA patients (EA-AD-MSC) to determine if EA-AD-MSC could be used for autologous tissue engineering approaches. Subcutaneous fat was obtained from pediatric patients undergoing surgery (IRB#). The cells from all patients expressed mesenchymal stem cell markers CD90, CD105, CD73, CD44 and did not express hematopoietic markers CD45, CD34 and HLA-DR by flow cytometry. Growth kinetics revealed similar population doubling times and morphology was similar between the two groups. Some of the EA-AD-MSC demonstrated upregulated expression of ATNX1, BMI1, FOXF1, GLI2, GLI3, MYC, HOXC4 and NOG, known genotypic abnormalities in EA patients. None of the N-AD-MSCs had upregulated expression of these genes. Furthermore N-AD-MSCs and EA-AD-MSCs underwent osteogenic and adipogenic differentiation with positive staining for Oil Red O and Alizarian Red after 2 weeks in culture. The integrin profiles of these cells were also similar across all patients as demonstrated by flow cytometry. In conclusion, in vitro, the EA-AD-MSCs behaved similarly to N-AD-MSCs in growth kinetics, mesenchymal phenotype and differentiation ability. Genotypically there were some differences and how this will impact the growth of these cells on scaffolds is currently being investigated.